Regionalisation of competition regulation in ASEAN: Prospects and challenges - Ahamat, Haniff; Abdul Rahman, Nasarudin (2013)

(untitled)
The AEC has required competition law to be introduced in ASEAN Member States (AMS) by 2015. The AEC blueprint has been cited as one of the key factors driving the Malaysian Government into passing the Competition Act 2010. In fact the ASEAN Regional Guidelines on Competition Policy 2010 was drafted to serve as a general framework for AMS to introduce, implement and enforce competition policy and law. However, there is also no regional body overseeing the administration of such laws at the ASEAN level the creation of such body may be hindered by the lack of consistency between existing competition laws in AMS and different political, economic and legal environments there. This results in the regional context of competition regulation in ASEAN being limited to international cooperation and utilization of extra-territorial power of AMC CRBs. However the latter may pose several challenges including the use of competition regulation as a barrier to intra-ASEAN trade and beyond.